Celecoxib solid dispersion with solubilizing property and high drug loading capacity and preparation method of celecoxib solid dispersion

By using binary polymers composed of carrier materials and crystal inhibitors, a solid dispersion of celecoxib with high drug loading was prepared, which solved the problems of poor solubility and low drug loading, and achieved the drug efficient absorption and stability.

CN119424455AActive Publication Date: 2025-02-14ZHEJIANG UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411564076.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

The poor solubility of celecoxib leads to its low oral bioavailability, limiting its clinical application. The existing amorphous solid dispersions have low drug loading, making it difficult to achieve efficient drug absorption.

Method used

A high drug-loaded celecoxib solid dispersion is prepared by using carrier materials with good solubilization properties such as polyacrylic resin (EPO) and crystal inhibitors such as copovidone VA64.

Benefits of technology

The high drug loading (up to 50%) and good dissolution performance of celecoxib were achieved, and the problem of sharp decline in dissolution when the drug loading was increased was overcome, and the absorption efficiency and storage stability of the drug were improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005118726500000011
    Figure BDA0005118726500000011
  • Figure HDA0005118726510000011
    Figure HDA0005118726510000011
  • Figure HDA0005118726510000012
    Figure HDA0005118726510000012
Patent Text Reader

Abstract

The invention discloses a high-drug-loading-capacity celecoxib solid dispersion with solubilizing performance and a preparation method thereof. The solid dispersion is prepared from the following components in percentage by mass: 50% of celecoxib, 40-47% of a carrier material and 3-10% of a crystal inhibitor, the total percentage of all the components is 100%. Wherein the carrier material is polyacrylic resin; the crystal inhibitor is selected from one or more of copovidone VA64, povidone K30, hydroxypropyl methylcellulose E5 and hydroxypropyl methylcellulose E50; the solid dispersion provided by the invention has high dissolution rate and good stability, and can effectively inhibit recrystallization of a drug in a supersaturated solution and maintain the supersaturation degree of the drug in the solution; according to the present invention, the carrier-crystal inhibitor binary polymer combination is adopted to achieve the complete release of the drug, and the new idea is provided for the preparation or the process innovation of the high drug loading capacity celecoxib preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of pharmaceutical preparations, and particularly relates to a high-drug-loading celecoxib solid dispersion with solubilization performance and a preparation method thereof. Background Art

[0002] Celecoxib is a 1,5-diaryl substituted pyrazole compound, with the chemical name 4-[5-(4-methylphenyl)-3-(trifluoromethyl)-1-hydrogen-1-pyrazol-1-yl]benzenesulfonamide. It is the world's first selective COX-2 inhibitor non-steroidal anti-inflammatory drug. It is mainly used clinically to treat acute pain and relieve the symptoms and signs of osteoarthritis, rheumatoid arthritis and ankylosing spondylitis. Its advantage is that it can relieve symptoms without causing related gastrointestinal complications. Its chemical structure is as follows:

[0003]

[0004] Celecoxib has poor solubility, high hydrophobicity and high permeability, and belongs to BCS class II drugs. Its solubility in water at 25°C is only 0.007 mg / mL, and its dissolution rate in gastrointestinal fluid after oral administration is slow, resulting in low oral bioavailability, which seriously affects its efficacy and greatly limits its clinical application. Therefore, improving the solubility and dissolution rate of celecoxib is the primary problem to be overcome in the research and development of its oral preparations.

[0005] At present, in order to improve the dissolution rate and in vivo absorption of celecoxib, there are multiple drug solubilization technologies that have been applied to the research and development of celecoxib preparations, such as nanocrystals, amorphous solid dispersions, inclusion compounds, liposomes, etc. Among them, amorphous solid dispersions are a typical supersaturated drug delivery system, which produces supersaturated concentration by increasing the solubility or dissolution rate of the drug to increase the absorption of the drug. However, this supersaturated solution is in a thermodynamic metastable state, and the drug is easily converted into a stable crystalline state in the gastrointestinal tract. Therefore, in order to maintain the highly dispersed state of the drug and the stability of the supersaturated solution, a large amount of polymer carriers are often added during the preparation of solid dispersions, so that the drug loading of amorphous solid dispersions is usually relatively low. When the drug loading is too high, the dissolution rate of the solid dispersion becomes the drug-controlled type from the carrier-controlled type, so that the dissolution rate is sharply reduced, and even the solubilization advantage of the solid dispersion is lost. Therefore, low drug loading is a common problem of amorphous solid dispersions, and the celecoxib solid dispersion reported now is no exception. Chinese patent CN103655478A discloses a celecoxib solid dispersion and its preparation method and application, celecoxib and poloxamer 188 are prepared into solid dispersion by melting method or solvent method, the solubility of the drug is increased, but the drug loading is only 4.7% to 16.6%. Chinese patent CN102000018 A discloses a solid dispersion containing celecoxib and its preparation method and application, preferably the drug loading is 33.3%, and the final tablet and capsule preparation specifications are larger. This makes the patient take a large amount of auxiliary materials when taking the therapeutic dose, often because the product dosage is too large and reduces the patient's compliance, and increases the cost of auxiliary materials. Therefore, it is of great significance to develop a high drug loading celecoxib solid dispersion with good solubility performance.

[0006] The present invention adds a small amount of crystal inhibitor on the basis of selecting a carrier with good solubilizing performance, and inhibits or slows down the precipitation process of the drug supersaturated solution by interfering with the formation and growth of crystal nuclei to prolong the supersaturation maintenance time, thereby exerting a good "spring-parachute" effect. By rationally combining the carrier and the crystal inhibitor binary polymer, a celecoxib solid dispersion with a drug loading of up to 50% and good dissolution performance is successfully prepared. Summary of the invention

[0007] The present invention aims to provide a high-drug-loading celecoxib solid dispersion with good solubilization performance and a preparation method thereof, so as to overcome the limitation of low drug-loading amount of the current celecoxib solid dispersion.

[0008] The solid dispersion prepared by the present invention can rapidly dissolve celecoxib at a high drug loading, and improves the storage stability of the celecoxib solid dispersion.

[0009] The technical solution of the present invention is as follows:

[0010] A celecoxib solid dispersion is prepared from the following components in percentage by mass:

[0011] Celecoxib 50%, carrier material 40-47%, crystal inhibitor 3-10%; all components total 100%;

[0012] in,

[0013] The carrier material is polyacrylic acid resin, preferably EPO;

[0014] The crystal inhibitor is selected from one or more of copovidone VA64 (PVP VA64), povidone K30 (PVP K30), hydroxypropyl methylcellulose E5 (HPMC E5), and hydroxypropyl methylcellulose E50 (HPMC E50); preferably copovidone VA64.

[0015] Particularly preferably, the celecoxib solid dispersion of the present invention is made of the following components in mass percentage:

[0016] Celecoxib 50%, EPO 45%, copolyvidone VA64 5%.

[0017] The preparation method of the celecoxib solid dispersion of the present invention is as follows:

[0018] Weigh celecoxib, a carrier material, and a crystal inhibitor in a solvent, mix them evenly, then remove the solvent by rotary evaporation, vacuum dry, grind and sieve to obtain a celecoxib solid dispersion;

[0019] The solvent is a mixed solvent of anhydrous ethanol and dichloromethane, preferably the volume ratio of anhydrous ethanol to dichloromethane is 3:1;

[0020] Preferably, the rotary evaporation temperature is 50°C and the vacuum drying temperature is 50°C;

[0021] Preferably, the powder is ground through a 120 mesh screen.

[0022] The beneficial effects of the present invention are embodied in:

[0023] The present invention fully utilizes the supersaturation advantage of high drug loading solid dispersions by using suitable carriers and crystal inhibitors, which can effectively inhibit the crystal nucleation and growth of the drug in the supersaturated solution, so that the drug can be dissolved quickly and completely, overcoming the common "cliff effect" of a sharp drop in dissolution when the drug loading increases. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 : Dissolution curve of the solid dispersion of Example 1 in pH=1 medium.

[0025] Figure 2: Dissolution curves of the solid dispersions of Example 2 and Example 3 in a pH=1 medium.

[0026] Figure 3 : Dissolution curves of the solid dispersions of Example 4 and Example 5 in a pH=1 medium.

[0027] Figure 4 : Differential scanning calorimetry of the bulk drug and the solid dispersion of Example 4.

[0028] Figure 5 : X-ray diffraction patterns of the raw material and the solid dispersion of Example 4

[0029] Figure 6 : Powder X-ray diffraction pattern of the stability investigation experiment of the solid dispersion of Example 4.

[0030] Figure 7 : Dissolution curve of the stability investigation experiment of the solid dispersion of Example 4.

[0031] Figure 8 : Dissolution curves of the solid dispersions of Example 4, Comparative Example 1 and Comparative Example 2 in a pH=1 medium. DETAILED DESCRIPTION

[0032] The technical scheme of the present invention is clearly and completely described below by specific embodiments in conjunction with the accompanying drawings. It should be noted that the following description is only for explaining the present invention and does not limit its content. Unless otherwise specified, the content of each component used below is the weight percentage content.

[0033] Embodiment 1:

[0034] Weigh 3g of celecoxib, 2.7g of EPO and 0.3g of HPMC E50 were mixed evenly and added to 30mL of a mixed solution of anhydrous ethanol and dichloromethane (mixed in a volume ratio of 3:1). After ultrasonic dissolution, the solvent was evaporated under reduced pressure at 50°C using a rotary evaporator, and then transferred to a vacuum drying oven at 50°C and dried overnight. Finally, the solid dispersion was obtained by grinding and sieving through a 120-mesh sieve.

[0035] Weigh three portions of 0.100g of solid dispersion and put them into 900mL of hydrochloric acid solution with pH=1 respectively. Perform dissolution test according to the paddle method in the 2020 edition of the "Chinese Pharmacopoeia" dissolution test, with a rotation speed of 50rpm. Take samples at 2, 5, 10, 20, 30, 45, and 60min respectively. After rapid filtration, use UV-visible spectrophotometry to determine the drug concentration and calculate the cumulative dissolution percentage at each time point. Take three portions of 50mg of celecoxib raw material respectively, operate in the same way, and determine the cumulative dissolution percentage at each time point. See the results. Figure 1 .from Figure 1 It can be seen that the solubility of celecoxib raw material in hydrochloric acid is very small, and the dissolution in 60 minutes is only 0.7%. EPO was used as a carrier and HPMC E50 as an inhibitor. After being made into a solid dispersion, the solubility of celecoxib increased dramatically. At 60 minutes, the solubility of celecoxib was 68.97%, which was much higher than that of the raw material.

[0036] Embodiment 2:

[0037] Weigh 3g of celecoxib, 2.7g of EPO and 0.3g of HPMC E5 were mixed evenly and added to 30mL of anhydrous ethanol and dichloromethane mixed solution (mixed in a volume ratio of 3:1). After ultrasonic dissolution, the solvent was evaporated under reduced pressure at 50°C using a rotary evaporator, and then transferred to a vacuum drying oven at 50°C and dried overnight. Finally, the solid dispersion was obtained by grinding and sieving through a 120-mesh sieve.

[0038] Weigh 0.100g of the solid dispersion three times and put them into 900mL of pH=1 hydrochloric acid solution respectively, and perform the powder dissolution test according to the method of Example 1. Figure 2 .from Figure 2 It can be seen that after adding HPMC E5 as an inhibitor, the dissolution rate of celecoxib was 79.13% at 60 min.

[0039] Embodiment 3:

[0040] Weigh 3g of celecoxib, 2.7 g of EPO and 0.3 g of PVP K30 were mixed evenly and added to 30 mL of anhydrous ethanol and dichloromethane mixed solution (mixed in a volume ratio of 3:1). After ultrasonic dissolution, the solvent was evaporated under reduced pressure at 50°C using a rotary evaporator, and then transferred to a vacuum drying oven at 50°C and dried overnight. Finally, the solid dispersion was obtained by grinding and sieving through a 120-mesh sieve.

[0041] Weigh 0.100g of the solid dispersion three times and put them into 900mL of pH=1 hydrochloric acid solution respectively, and perform the powder dissolution test according to the method of Example 1. Figure 2 .from Figure 2 It can be seen that after adding PVP K30 as an inhibitor, the solubility of celecoxib was 83.16% at 60 min, showing good dissolution performance.

[0042] Embodiment 4:

[0043] Weigh 3g of celecoxib, 2.7 g of EPO and 0.3 g of PVP VA64 were mixed evenly and added to 30 mL of anhydrous ethanol and dichloromethane mixed solution (mixed in a volume ratio of 3:1). After ultrasonic dissolution, the solvent was evaporated under reduced pressure at 50°C using a rotary evaporator, and then transferred to a vacuum drying oven at 50°C and dried overnight. Finally, the solid dispersion was obtained by grinding and sieving through a 120-mesh sieve.

[0044] Weigh 0.100g of the solid dispersion three times and put them into 900mL of pH=1 hydrochloric acid solution respectively, and perform the powder dissolution test according to the method of Example 1. Figure 3 .from Figure 3 It can be seen that after adding PVP VA64 as an inhibitor, the solubility of celecoxib was 90.73% at 60 min, showing excellent dissolution performance, and at the same ratio, the inhibitory performance of PVP VA64 was better than that of HPMC E50, HPMC E5 and PVP K30.

[0045] Embodiment 5:

[0046] Weigh 3g of celecoxib, EPO 2.82g, VA64 0.18g were mixed evenly and added to 30mL of anhydrous ethanol and dichloromethane mixed solution (mixed in a volume ratio of 3:1). After ultrasonic dissolution, the solvent was evaporated under reduced pressure at 50°C using a rotary evaporator, and then transferred to a vacuum drying oven at 50°C and dried overnight. Finally, the solid dispersion was obtained by grinding and sieving through a 120-mesh sieve.

[0047] Weigh 0.100g of the solid dispersion three times and put them into 900mL of pH=1 hydrochloric acid solution respectively, and perform the powder dissolution test according to the method of Example 1. Figure 3 .from Figure 3 It can be seen that after adding 3% PVP VA64, the solubility of celecoxib was 80.88% at 60 min, showing good dissolution performance.

[0048] Embodiment 6:

[0049] About 5 mg of the solid dispersion prepared in Example 4 was weighed into an aluminum pot, and the thermal behavior of the sample was detected by differential scanning calorimetry. The nitrogen flow rate was 50 mL / min, the heating rate was 10°C / min, and the scanning range was 25°C to 200°C. 5 mg of the physical mixture and celecoxib raw material in the same proportion as in Example 4 were taken and operated in the same manner. The obtained spectrum is shown in FIG. Figure 4 .

[0050] As can be seen from the figure, the celecoxib raw material has a strong endothermic peak at 161.6°C, which is its melting point. The solid dispersion does not have this endothermic peak, indicating that the celecoxib crystals have disappeared and are dispersed in the carrier material in an amorphous form. The resulting product is an amorphous solid dispersion. The disappearance of the melting point peak of the drug in the physical mixture indicates that the drug melts in the polymer material during the heating process.

[0051] Take appropriate amounts of celecoxib raw material, Example 4 and the physical mixture of Example 4 in the same proportion, and measure the diffraction pattern thereof by powder X-ray diffraction method. The results are shown in FIG. Figure 5 .from Figure 5 As can be seen in the scanning interval, the celecoxib bulk drug shows strong crystal diffraction peaks at 10.74°, 14.9°, 16.16°, 19.7°, and 21.54° at 2θ. The strong sharp diffraction peaks of the celecoxib bulk drug do not appear in the solid dispersion obtained in Example 4, indicating that the products obtained in Example 4 are amorphous solid dispersions. The crystal peaks that appear in the physical mixture overlap substantially with the crystal peaks of the bulk drug.

[0052] Embodiment 7:

[0053] The solid dispersion obtained in Example 4 was placed in an environment with a temperature of 40°C and a relative humidity of 75% for stability test. The solid dispersion was taken out at 0, 1, 2, and 3 months and the crystal structure of the drug was characterized by powder X-ray diffraction. Another 0.100 g sample was weighed and put into 900 mL of hydrochloric acid solution with a pH of 1 for powder dissolution test. The experiment was carried out in three parallel groups. Figure 6 : is the X-ray diffraction pattern of the obtained powder. It can be seen that the obtained solid dispersion does not show a strong and sharp diffraction peak within three months, proving that the amorphous morphology is maintained. Figure 7 ] is the obtained dissolution curve. There is no obvious difference between the dissolution curves, and all have excellent dissolution performance, which proves that the solid dispersion obtained in Example 4 has good stability.

[0054] Comparative Example 1:

[0055] Weigh 3g of celecoxib, 3 g of EPO was mixed evenly and added to 30 mL of a mixed solution of anhydrous ethanol and dichloromethane (mixed in a volume ratio of 3:1). After ultrasonic dissolution, the solvent was evaporated under reduced pressure at 50°C using a rotary evaporator, and then transferred to a vacuum drying oven at 50°C and dried overnight. Finally, the solid dispersion was obtained by grinding and sieving through a 120-mesh sieve.

[0056] Weigh 0.100g of the solid dispersion three times and put them into 900mL of pH=1 hydrochloric acid solution respectively, and perform the powder dissolution test according to the method of Example 1. Figure 8 . Although EPO can quickly improve the dissolution rate of celecoxib solid dispersion with 50% drug loading, it shows a typical "spring" effect, with a drug concentration of 21.54 μg / ml and a solubility of 34% at 2 minutes. However, due to the high supersaturation, the drug concentration is in a thermodynamically unstable amorphous state, so a sharp drop in drug concentration is observed after two minutes. After adding 5% PVP VA64 as a crystal inhibitor, a good crystal inhibition function is shown, and the solubility of celecoxib is 90.73% at 60 min, showing excellent dissolution performance.

[0057] Comparative Example 2:

[0058] Weigh 3g of celecoxib, 2.4 g of EPO and 0.6 g of VA64 were mixed evenly and added to 30 mL of a mixed solution of anhydrous ethanol and dichloromethane (mixed in a volume ratio of 3:1). After ultrasonic dissolution, the solvent was evaporated under reduced pressure at 50°C using a rotary evaporator, and then transferred to a vacuum drying oven at 50°C and dried overnight. Finally, the solid dispersion was obtained by grinding and sieving through a 120-mesh sieve.

[0059] Weigh 0.100g of the solid dispersion three times and put them into 900mL of pH=1 hydrochloric acid solution respectively, and perform the powder dissolution test according to the method of Example 1. Figure 8 .from Figure 8 It can be seen that after adding 10% PVP VA64, the dissolution rate of celecoxib was only 54.89% at 60 minutes. Compared with the addition of 5% PVP VA64, the dissolution rate slowed down significantly with the increase of the proportion of the anti-crystal agent, which had a negative impact on hindering the dissolution of the drug.

Claims

1. A celecoxib solid dispersion, characterized in that: Made of the following components in mass percentage: Celecoxib 50%, carrier material 40-47%, crystal inhibitor 3-10%; all components total 100%; in, The carrier material is polyacrylic acid resin; The crystal inhibitor is selected from one or more of copovidone VA64, povidone K30, hypromellose E5, and hypromellose E50.

2. The celecoxib solid dispersion according to claim 1, characterized in that The carrier material is EPO.

3. The celecoxib solid dispersion according to claim 1, characterized in that The crystal inhibitor is copolyvidone VA64.

4. The celecoxib solid dispersion according to claim 1, characterized in that The celecoxib solid dispersion is made of the following components in percentage by mass: Celecoxib 50%, carrier material 45%, crystal inhibitor 5%; in, The carrier material is EPO; The crystal inhibitor is copolyvidone VA64.

5. The method for preparing the celecoxib solid dispersion according to claim 1, wherein: The preparation method is as follows: Weigh celecoxib, carrier material and crystal inhibitor in a solvent and mix them evenly, then remove the solvent by rotary evaporation, vacuum dry, grind and sieve to obtain celecoxib solid dispersion.

6. The preparation method according to claim 5, characterized in that: The solvent is a mixed solvent of anhydrous ethanol and dichloromethane.

7. The preparation method according to claim 6, characterized in that: The solvent is a mixed solvent of anhydrous ethanol and dichloromethane in a volume ratio of 3:

1.

8. The preparation method according to claim 5, characterized in that: The rotary evaporation temperature was 50°C, and the vacuum drying temperature was 50°C.

9. The preparation method according to claim 5, characterized in that: Grind through a 120 mesh sieve.

Citation Information

Patent Citations

  • Solid dispersion containing celecoxib as well as preparation method and application thereof

    CN102000018A

  • Celecoxib solid dispersion and preparation method and application thereof

    CN103655478A

  • Celecoxib solid dispersion and preparation method thereof

    CN102988296A

  • Celecoxib-containing solid dispersion and preparation method thereof

    CN103371976A

  • Celecoxib pharmaceutical composition and preparation method thereof

    CN108524527A